Pengenalan Penanganan Limbah Domestik dengan Takakura Composting Method (TCM) pada Kelompok Karang Taruna di Desa Patampanua Kabupaten Soppeng - Andi Dian Sry Rezki Natsir (Faculty of Engineering UNHAS, 2023)
Community Service is one of the primary responsibilities of a lecturer, especially at ATI Makassar Polytechnic. This community service was held in the second week of September 2021 and is located in Patampanua Village, Marioriawa District, Soppeng Regency. Activities involving local government and Karang Taruna Group members have been carried out successfully and meet the objectives of implementing domestic waste treatment recognition activities with Takakura Methods. The method used to measure the program's impact was carried out using pre-test and post-test questionnaires to measure the participants' knowledge changes. The average value of pre-test results (6.00) given before giving material or introducing domestic waste treatment activities with the Takakura method is lower than the average post-test value (18.00) of respondents. This increase in average scores for both groups of respondents' values indicates an initial estimation that respondents gained increased knowledge from these activities. The argument is also supported by the results of the paired t-test (Sig. 0,00), where the hypothesis is that there is an average difference between pre-test data with post-test data. It shows that there is an influence on material giving and learning on improving the respondents' understanding.